Transcriptional regulation of copper metabolism genes in the liver of fetal and neonatal control and iron-deficient rats - Lenartowicz, Malgorzata; Kennedy, Christine; Hayes, Helen; McArdle, Harry J. (Biometals, 2015)
Copper and iron metabolism have been known to interact for many years. We have previously shown, during pregnancy, that copper levels in the maternal liver rise as a consequence of iron deficiency, but that levels in the fetal liver decrease. In this paper, we measure expression of genes involved in copper metabolism in fetal and postnatal liver, to test whether alterations can explain this observation. Additionally, we study the extent to which gene expression changes in the latter stages of pregnancy and in the perinatal period. Ctr1 expression levels dropped to term, rising again thereafter. There was no difference in gene expression between control and iron deficient animals. Atox1 expression remained approximately stable until term, and then there was a rise to a maximum at about Day 8. Atp7a expression levels remained constant, except for a brief drop at term. Atp7b levels, in contrast, decreased from a maximum early in gestation to low levels in the term and post-natal livers. Ceruloplasmin expression appeared to be diametrically opposite to Atp7b . The other two metallochaperones showed the same pattern of expression as Atox1 , with a decrease to term, a rise at Day 1, or a rise after birth followed by a brief decrease at about Day 3. None of the genes were significantly affected by iron deficiency, suggesting that changes in expression cannot explain the altered copper levels in the fetal and neonatal liver.